国後島およびサハリン産野ネズミ類の寄生線虫類 - Asakawa, M; 6756; Pavlenko, Marina V.; 6757; Kartavtseva, Irina V.; 6758; Tsuchiya, Kimiyuki; 6759; Moriwaki, Kazuo; 6760; Harada, Masashi; 6761 (日本生物地理学会, 1994)
Article As a part of an insular zoogeographical research project, an analysis was made of the parasitic nematode fauna of 61 individuals of 5 rodent species, viz., Apodemus speciosus [abbreviated to As], A. peninsulae [abbreviated to Ap], A. agrarius [abbreviated to Aa], Clethrionornys rufocanus [abbreviated to Crf], C. rutilus [abbreviated to Crt], collected on Kunashir and Sakhalin Islands, plus our findings in Primorskiy Region, Russia. Among them following nematode species were obtained; Syphacia agraria [As, Ap, Aa], S. montana [Crf], S. spp. [Crf, Ap, Aa], Heligmosomoides kurilensis [As], H. neopolygyrus [Ap, Aa], H. sp. [Ap, Aa], Heligmosomum (Paraheligmosomum) yamagutii [Crf], H. (P.) sp. [Crt], Heligrnonoides speciosus [As], H. sp. [Ap], Rhabditis (Pelodera) orbitalis (3rd-stage larva) [Crt], Rictularia cristata [Ap, Aa], Heterakis spumosa [Aa], Toxocara apodemi [Aa], Eucoleus sp. [Aa], Nematoda fam. gen. sp. (encysted larva) [Aa]. Although these nematode species have been reported from Hokkaido, this is the first report of S. agraria and H. speciosus on Kunashir Island, and of S. agraria, H. neopolygyrus and R (P.) orbitalis on Sakhalin Island, respectively. S. agraria, H. neopolygyrus, R. cristata and T. apodemi have been reported from the Eastern Part of Chinese Continent. However, it is first that these nematode species were obtained from Primorskiy Region. Furthermore, Heligmonoides sp. obtained from A. peninsulae showed a close similarity with the nematode reported from A. agrarius in Shenyang, China. Hence, the main nematode fauna of Apodemus spp. of Primorskiy Region accorded almost with the fauna of the Eastern Part of Chinese Continent. journal article